2012
DOI: 10.1590/s0104-14282012005000040
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de filmes de nananocompósitos polipropileno/argila organofílica para embalagens

Abstract: Resumo: Neste trabalho foram preparados filmes de nanocompósitos de polipropileno (PP) contendo 1% em massa de bentonita modificada organicamente com tecnologia nacional (APO). Polipropileno enxertado com anidrido maleico (PP-g-AM) e copolímero de etileno e álcool vinílico (EVOH) foram utilizados como agentes compatibilizantes. Os nanocompósitos foram preparados através da intercalação no estado fundido em extrusora de filme plano. A influência do tipo e do teor de compatibilizante e do tipo de polipropileno, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Similar results were obtained by Lee, Mielewski and Baird, Araújo et al , who studied PP/OMMT/PP‐g‐MA nanocomposites and concluded that the addition of compatibilizer promotes a disordered intercalated structure tending to exfoliation.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were obtained by Lee, Mielewski and Baird, Araújo et al , who studied PP/OMMT/PP‐g‐MA nanocomposites and concluded that the addition of compatibilizer promotes a disordered intercalated structure tending to exfoliation.…”
Section: Resultssupporting
confidence: 86%
“…Various strategies have been used to improve the properties of PP, such as the use of inorganic fillers in combination with coupling agents to obtain PP nanocomposites with good thermal stability, flame resistance, mechanical properties, among others …”
Section: Introductionmentioning
confidence: 99%